Factors Affecting Glycemic Control in Type-1 Diabetes Mellitus in Patients Visiting Newly Established Diabetic OPD at Tertiary Car Hospital Hyderabad Sindh - Noor U Ddin Khatti, Abdul Hameed Radhan, Ghulam Shabir Laghari, Muhammad Sohail Qaimkhani, Shamaeel, Saeed Ahmed Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients worldwide are affected by diabetes mellitus (DM), one of the most frequent diseases in the world. Various organs and systems in the body are affected by diabetic complications, which can be either microvascular or macrovascular in nature. Finding out and preventing these variables is critical to improving the quality of life for diabetics. Objective: To assess the poor glycemic control and its association with affected factors it in our diabetes population. Material and Methods: This Observational study was conducted on 80 patients in the Department of Pediatric (Unit II), Liquate University Hospital, Jamshoro/Hyderabad for six months from 1st January to 30th June 2021. Diabetic children between the ages of 1 and 15 who had Type-1DM and were on insulin therapy at LUMHS Hospital Jamshoro/Hyderabad were eligible for inclusion. Using a pre-tested structured questionnaire, we asked particular questions of each child after they had been inspected and their family history was gathered. Data was analyzed using SPSS version 26.0 Results: A total of 80 patients were enrolled in this study. Table: 1 shows the age and gender profile of the children. The most of the children were in the age group 5 to 12 years, with a p-value of 0.0001. As demonstrated in Table 2, the Subject had Polyuria, Polydipsia, Polyphagia, Fatigability and weight loss due to Diabetic ketoacidosis, the prevalence of consanguinity in the family, average monthly earnings, and the cost of insulin and glucose control. Table 3 shows weight and height. Graph I (p=0.0001) reveal that 14 (17.5%), 17 (21.2%), and 49 (61.2%) participants had good, fair, or poor glycemic control, respectively. Conclusion: Uncontrolled diabetes and complications are linked to poor insulin adherence, which is the mainstay of treatment. It is suggested that this topic be explored further.